Enhancing Green Campus Sustainability through Mental Model Development: An Islamic Perspective - Heru Juabdin Sada (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2023)
This study explores the pivotal role of mental model development in enhancing sustainability initiatives within green campuses. As universities increasingly strive to mitigate their environmental impact, understanding and fostering the mental models of students, faculty, and staff becomes crucial. Mental models, which are deeply ingrained assumptions and perspectives about how the world works, significantly influence individuals' behaviors and decision-making processes. By identifying and reshaping these mental models to align with sustainability goals, educational institutions can cultivate a more sustainable campus culture. The research employs a qualitative approach with data from university leaders and faculties. Data collection techniques are interviews, observation, documentation, and questionnaires. The researcher analyzed the data using Nvivo 12Plus software through 7 stages: open coding, axial coding, selective coding, matrix coding query, and word frequency query. The results of the analysis show that, through the democratic attitude of the leaders and staff in each unit, the campus community members can express their opinions and can be well received by the leaders and staff. With a resilient mentality, every problem can be adequately resolved, and they are able to appreciate and manage diversity and not impose their will. Leaders, with material rewards, appreciate the office boys or staff at UIN Raden Intan.